Nutritional Status Assessment Using WHO Z-Scores (BMI For Age) In Children Aged 6-15 Years – A Study from Central India - Gupta, Manmohan; Borle, Amod; Chhari, Neeraj; Gupta, Sanjay (National Journal of Community Medicine, 2015)
Introduction: National family health survey (NFHS)-3 conducted in India recently has not reported on nutritional status of children in 6 -15 years age group. So this study was carried out to assess the nutritional status of the children aged 6- 15 years of age using WHO z-score for BMI for age and its socio-demographic correlates in urban area of Bhopal, Madhya Pradesh. Methodology: Cross sectional study was carried out among children of 6-15 years age group residing in field practice area of urban health training centre (UHTC) of a medical college in Bhopal.270 children were enrolled in study 54 children were selected from each one of the five localities catered by UHTC. Data was collected with the interview technique followed by anthropometric measurements by door to door survey. Results: The prevalence of under nourishment was 51.1% with prevalence of thinness 37.4% and of severely thin 13.7%. Variables such as sex, age, education of mother, occupation of mother, Education & occupation of father, number of siblings were found to be significant on bivariate analysis. When controlling for other variables, sex, Education of mother and occupation of mother were found to be significant and other variables lost their significance on binary logistic regression analysis. Conclusions: Sex, Mothers education and occupation were some of the correlates which are significantly related with nutritional status of children in 6-15 years age group.